The Effects of HIV/AIDS Education on Knowledge, Attitude, and Satisfaction for AIDS Prevention Self Massage on College Students in Korea (Medico Legal Update, 2020)
Background/Objectives: It is important to provide education for university students about HIV/AIDS. This study was to evaluate the effects of HIV/AIDS education program in knowledge, attitudes of HIV/AIDS, and satisfaction of education.Methods/Statistical analysis: The research design was a nonequivalent control group pretest-posttest design. The participants were comprised of 102 students (experimental group=50, control group=52) in Korea. A self-questionnaire knowledge and attitudes about HIV/AIDS were administered before, and after 180 minutes of HIV/AIDS education. The collected data was analysed descriptive statistics, Chi-square test, and t-test.Findings: There were significant differences in the mean scores of knowledge, and attitude of HIV/AIDS and were significant differences satisfaction of education between two groups.Improvements/Applications: HIV/AIDS education including multimedia was found to be an effective method for increasing knowledge, and atttitudes of AIDS/HIV. The results suggest that customized educational programs with methods and contents should be developed to improve knowledge, exciting and participation of the learners.